Officer Attitudes and Management Influences on Police Work Productivity - Johnson, Richard Ronald (American journal of criminal justice, 2011)
Police officers are afforded a high degree of discretion in the exercise of their authority, and the control of this discretion is an important issue. While it is assumed that individual officer attitudes and preferences shape their discretionary activity, these officers are also members of a paramilitary organization with leaders appointed over them. The present study explored the influence of both officer attitudes and supervisor influences to explain variation in officer traffic citation issuing rates. Hierarchical linear modeling was used with a sample of 312 patrol officers and 60 supervisors from 21 municipal police agencies. The results revealed that both officer occupational attitudes and supervisor influences (through informal rewards and behavior modeling) significantly influenced the degree to which officers issued traffic citations. The findings emphasize the need for both the supervision of officers and the shaping of officer attitudes in the control of officer discretion.